Awareness on wound cleaning and dressing among nursing undergraduates in university of peradeniya, sri lanka - Haththotuwa, T.N.; Wijesundara, W.M.C.C. (University of Jaffna, 2018)
Wound cleaning and dressing is one of the main responsibilities of nurses and nursing undergraduates. Better awareness on wound cleaning and dressing minimizes the wound infections, healing time, pain during the procedure, as well as duration of hospital stay. Indirectly this will minimize the government expenditure on wound management and enhances the patient’s quality of life. According to the literature review, a paucity of research exists that describes nurses’ awareness on wound cleaning and dressing. Published data regarding this aspect in Sri Lanka also scares. Therefore, this study was aimed to assess the current awareness among nursing undergraduates of Faculty of Allied Health Sciences, University of Peradeniya, Sri Lanka. A descriptive, cross-sectional study was carried among one hundred and fifty-one (n=151) nursing undergraduates using a self- administered questionnaire conducted from March to June, 2016. The questionnaire was piloted with 10 nursing students and ethical clearance was obtained from the Ethical Clearance Committee in Faculty of Allied Health Sciences, University of Peradeniya. Data were analyzed using Microsoft Excel and R-studio statistical software. Overall, their average knowledge score was 68 % (SD 12.5%) and the study revealed that nursing undergraduates of Faculty of Allied Health Sciences, University of Peradeniya are having sound knowledge on aseptic techniques to follow during wound cleaning and dressing (mean score 78%). Though, there are gaps in their knowledge with respect to different wound cleaning solutions and techniques, management of special wounds such as burn wounds, venous/diabetic ulcers, neonatal/infant wounds as well as newly available dressing products in the market. Therefore, it is better to develop an effective educational program to enhance the awareness and supervise undergraduates closely while performing rather than rely on self reported data. Moreover, results of this study cannot be generalized to the whole population of nursing undergraduates in Sri Lanka. Therefore, it is suggested to repeat the study in representative samples from both public and private institutions that offer nursing degree in Sri Lanka.
Keywords: Awareness; Nursing undergraduates; Wound cleaning; Wound dressing